New Perspectives in the Fight Against Multidrug-Resistant Bacteria: The Potential of Endolysin Biocomposites - Carlos E. Camacho-González; Cesar S. Cardona-Felix; Alejandro Pérez-Larios; Víctor M. Zamora-Gasga; Sonia G. Sáyago-Ayerdi; Jorge A. Sánchez-Burgos (Antibiotics)
The growing threat of multidrug-resistant bacteria requires innovative therapies beyond traditional antibiotics. This review highlights the potential of endolysin biocomposites using alginate oligosaccharides (AOSs) and modified cellulose (CL) as stabilizers. AOSs could enhance endolysin stability and potentially support colonic fermentation, producing short-chain fatty acids that may synergize with endolysins to combat pathogens and improve gut health. KZ144 and LysPA26 are proposed as optimal candidates for their broad pH range, divalent cation tolerance, and potential effectiveness against Gram-positive and Gram-negative pathogens. Integrating AOSs and CL into biocomposites could offer a novel dual-action strategy against gastrointestinal diseases while potentially reducing antibiotic dependence.